Modulating drug release from poly(lactic-co-glycolic acid) thin films through terminal end-groups and molecular weight - Boey, Freddy Yin Chiang (2014)
Biodegradable PLGA is commonly employed for controlled drug release on the order of weeks to months. Hydrophobic drugs distribute homogeneously in PLGA, but their strong hydrophobic interaction typically results in narrow release profiles. In this study, three molecular weights (MW) and two different terminal end-groups of biodegradable PLGA were applied to broaden the range of drug release and vary the mechanical properties without the use of additives. Films knife-casted from PLGA polymers with terminal carboxylic acid end-groups were found to 1) absorb more water, 2) have higher rates of polymer mass loss, 3) increased hydrophobic drug release as compared to films knife casted from similar MW PLGA polymers with terminal ester end-groups. The highest drug release rates were obtained from low MW PLGA that had the densest surface concentration of terminal acid groups. An intermediate drug release profile was obtained with a blend of high and low MW PLGA. The various PLGA polymers (differing in MW, terminal groups, and combinations thereof) described herein could give rise to PLGA\PLGA blends that would allow independent tuning of drug release and mechanical properties without the inclusion of non-degradable additives with respect to hydrophobic, small molecule drugs.